Effect of electric field on heat transfer performance of automobile radiator at low frontal air velocity - S. Vithayasai (2018)
The effect of electric field on the performance of automobile radiator is investigated in this work. In this experiment, a louvered fin and flat tube automobile radiator was mounted in a wind tunnel and there was heat exchange between a hot water stream circulating inside the tube and a cold air stream flowing through the external surface. The electric field was supplied on the airside of the heat exchanger and its supply voltage was adjusted from 0 kV to 12 kV. From the experiment, it was found that the unit with electric field pronounced better heat transfer rate, especially at low frontal velocity of air. The correlations for predicting the air-side heat transfer coefficient of the automobile radiator, with and without electric field, at low frontal air velocity were also developed and the predicted results agreed very well with the experimental data. © 2006 Elsevier Ltd. All rights reserved.